Study of Stress Distribution in L-Shaped Walls with Openings under Intense Seismic Conditions on Various Soil Types - Salem Merabti; Salah Bezari (The Journal of Engineering and Exact Sciences)
This article contributes to deepening our understanding of the distribution of compression, tension, and shear stress in reinforced concrete mid-rise building shear walls. These L-shaped shear walls include openings that can account for up to 50% of the total wall area. To conduct this study, seismic performance analyses of the buildings were carried out using ABAQUS software on four distinct types of soils, subjecting the buildings to a high-intensity earthquake. Three wall thicknesses were considered: 15 cm, 20 cm, and 25 cm. The analysis results demonstrate that the use of thicker walls proved to be effective in reducing stresses, as expected, while also meeting the strength requirements. Furthermore, increasing the openings up to 30% in the shear walls allowed for a reduction in shear stress. However, it is important to note that the observed stresses varied depending on the type of soil and the percentage of openings in the walls.